Investigating the Influence of Think-Pair-Share Approach toward Students’ Reading Achievement - Sumekto, Didik Rinan (Bina Nusantara University, 2018)
This research aimed at investigating the influence of think-pair-share approach on the performance of ninth-grade students’ reading achievement. This classroom action research involved 35 public secondary school students in Pandowoharjo, Sleman, Special Region of Yogyakarta. They were selected by purposive sampling method. Data collection used the naturalistic observation technique and narrative reading text in the selected meetings. After a series of reading activity, a twenty-numbers multiple choice test was given to all respondents. Data were analyzed by using mixed analysis; self-reflective spiral model and descriptive statistics. Think-pair-share stimulated students’ participation and performance in reading, in which it increased the functional communication, discussion, decision taking, and conflict reduction in groups learning. The finding also showed that students’ mean of readed performance was 63,85 in the first cycle and increased to 66,00 in the second cycle. These cyclical outputs fulfill the minimal passing grade criteria. This research concludes that applying think-pair-share as a suitably alternative learning approach that helps the students develop their collaborative skills.